1997
DOI: 10.1037/0735-7044.111.5.920
|View full text |Cite
|
Sign up to set email alerts
|

Triple dissociation of anterior cingulate, posterior cingulate, and medial frontal cortices on visual discrimination tasks using a touchscreen testing procedure for the rat.

Abstract: Four experiments examined effects of quinolinic acid-induced lesions of the anterior cingulate, posterior cingulate, and medial frontal cortices on tests of visual discrimination learning, using a new "touchscreen" testing method for rats. Anterior cingulate cortex lesions impaired acquisition of an 8-pair concurrent discrimination task, whereas posterior cingulate cortex lesions facilitated learning but selectively impaired the late stages of acquisition of a visuospatial conditional discrimination. Medial fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
248
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(277 citation statements)
references
References 51 publications
25
248
3
1
Order By: Relevance
“…An additional comparison of sessions to criterion permitted comparison of the amount of time required for each rat to master each discrimination problem. We also considered whether more detailed analysis of intermediate criterion levels (e.g., sessions to move from chance performance to statistically above chance) might reveal effects on different phases of learning (e.g., Bussey et al, 1997). Because not all of the rats in Experiments 1C and 2 reached criterion on the central-cue visual-spatial discrimination, we were only able to analyze the sessions required to move from chance performance to above chance (61% correct).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional comparison of sessions to criterion permitted comparison of the amount of time required for each rat to master each discrimination problem. We also considered whether more detailed analysis of intermediate criterion levels (e.g., sessions to move from chance performance to statistically above chance) might reveal effects on different phases of learning (e.g., Bussey et al, 1997). Because not all of the rats in Experiments 1C and 2 reached criterion on the central-cue visual-spatial discrimination, we were only able to analyze the sessions required to move from chance performance to above chance (61% correct).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we sought to explore further the role of cholinergic MS/VDB neurons in visual-spatial conditional tasks, using computer-controlled automated tasks analogous to those used previously in nonhuman primates (Ridley et al, 1999) or in rats (Bussey et al, 1997(Bussey et al, , 2000. We found that lesions of MS/VDB cholinergic neurons were without effect on simple visual discriminations or on the double-cue visual-spatial conditional problem in which the animal responds to either the left or right object of an identical pair, contingent on which pair of objects was displayed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations